"Every soul shall taste death." Attitudes and beliefs of Moroccan muslim women living in Antwerp (Belgium) toward dying, death, and the afterlife. Issue 1 (2nd January 2019) - Ahaddour, Chaïma; Broeckaert, Bert; Van den Branden, Stef
ABSTRACT: This study aims to elicit the beliefs and attitudes of middle-aged and elderly Moroccan Muslim women toward dying, death, and the afterlife; to identify whether differences are observable between middle-aged and elderly participants and to document how the actual attitudes of our participants relate to normative Islamic literature. Interviews were conducted with middle-aged and elderly Moroccan women living in Belgium ( n = 30) and with experts in the field ( n = 15). This study reveals that the belief in an omnipotent and omniscient God and in an afterlife strongly marks the attitudes of first- and second-generation Muslims in Belgium toward life and death.